COMPARATIVE STUDY OF PHYTOCHEMICALS IN AQUEOUS AND SILVER NANOPARTICLES EXTRACTS OF AGROCYBE AEGERITA, (V. BRIG.)SINGER BLACK POPLAR MUSHROOM - NAGALAKSHMI MUTHU; KRISHNAKUMARI SHANMUGASUNDARAM (International Journal of Pharma and Bio Sciences, 2015)
The objective of the present study is to evaluate the phytochemical constituents of the mushroom Agrocybe aegerita (V. Brig.) Singer using four different extracts. Preliminary phytochemical screenings for various secondary metabolites were carried out. All the extracts both aqueous and silver nanoparticles were subjected to qualitative phytochemical screening and were analyzed for the presence of active constituents such as alkaloids, flavonoids, phenols, glycosides and triterpenoids. The generated data has provided the basis for its wide uses as a therapeutic both in traditional and folk medicine. The observed phytochemical constituents in the mushroom extract may be associated with its high bioactive constituents that may serve as candidates to new drugs in the treatment and prevention of various human ailments. The result obtained in the present study indicates Agrocybe aegerita mushroom have the potential to act as a source of useful drugs because of the presence of various primary and secondary metabolites.